2020
DOI: 10.1177/0269881120936419
|View full text |Cite
|
Sign up to set email alerts
|

The effects of acute cannabidiol on cerebral blood flow and its relationship to memory: An arterial spin labelling magnetic resonance imaging study

Abstract: Background: Cannabidiol (CBD) is being investigated as a potential treatment for several medical indications, many of which are characterised by altered memory processing. However, the mechanisms underlying these effects are unclear. Aims: Our primary aim was to investigate how CBD influences cerebral blood flow (CBF) in regions involved in memory processing. Our secondary aim was to determine if the effects of CBD on CBF were associated with differences in working and episodic memory task performance. Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
2

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 105 publications
1
37
2
Order By: Relevance
“…Additional data from this study have been published elsewhere; these previous reports did not investigate resting-state striato-cortical connectivity (Bloomfield et al, 2020; Lawn et al, 2020).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additional data from this study have been published elsewhere; these previous reports did not investigate resting-state striato-cortical connectivity (Bloomfield et al, 2020; Lawn et al, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…CC-BY-NC-ND 4.0 International license available under a (which was not certified by peer review) is the author/funder, who has granted bioRxiv a license to display the preprint in perpetuity. It is made The copyright holder for this preprint this version posted November 21, 2020. ; https://doi.org/10.1101/2020.11.20.391805 doi: bioRxiv preprint 8 Additional data from this study have been published elsewhere; these previous reports did not investigate resting-state striato-cortical connectivity (Bloomfield et al, 2020;Lawn et al, 2020).…”
Section: Studymentioning
confidence: 99%
“…However, these vernacular categories are unreliable for medical applications due to extensive cross-breeding and unreliable labeling during unrecorded hybridization (McPartland, 2017). CBD dominant and intermediate varieties were also excluded from these studies despite getting increasing attention from the therapeutic potential of CBD (Avraham et al, 2011;Bloomfield et al, 2020;French et al, 2017;McGuire et al, 2018), especially the indication of regulatory-approved prescription CBD (marketed as Epidiolex) to treat epilepsy (Billakota et al, 2019;Kaplan et al, 2017;Szaflarski et al, 2018). In addition to delimiting ''Sativa'' and ''Indica'' plants, recent studies tried to differentiate three chemotypes by profiling secondary metabolites (Jin et al, 2020), developing genetic markers (Borna et al, 2017;Kojoma et al, 2006;Pacifico et al, 2006;Rotherham et al, 2011;Toth et al, 2020), and comparing sequence and copy number variation of THC acid synthase and CBD acid synthase (McKernan et al, 2015;Onofri et al, 2015).…”
mentioning
confidence: 99%
“…Critically, our null findings for the effect of CBD on experimentally-induced stress are in contrast to previous findings reporting that CBD attenuated task-induced anxiety (Bergamaschi et al, 2011;Zuardi et al, 1993;Zuardi et al, 2017), and these discrepant findings may be due to the potentially dose-dependent nature of CBD's effects. Recent work suggests that CBD may have an inverted-U shape dose-response curve (Campos & Guimaraes, 2008;Freeman et al, 2020;Hsiao, Yi, Li, & Chang, 2012;Linares et al, 2019;Zuardi et al, 2017) with best efficacy for human anxiety at 300 mg (Linares et al, 2019;Zuardi et al, 1993;Zuardi et al, 2017) compared to our dose of 600 mg. However, the finding that CBD was able to reduce drug-cue-induced craving and anxiety at single doses of 400 mg and 800 mg (Hurd et al, 2019), suggests that our dose of 600 mg still falls within the effective range, and so our negative finding remains important as evidence against the anxiolytic hypothesis of CBD.…”
Section: Discussionmentioning
confidence: 79%
“…Lastly, three previous studies have found that chronic administration of CBD was anxiolytic: a 21day treatment of 600 mg of CBD was effective at reducing psychosis-related anxiety in patients at high-risk of psychosis, compared to placebo (Bhattacharyya et al, 2018) and a four-week treatment of oil with 300 mg of CBD significantly reduced anxiety in a socially anxious sample, compared to placebo (Masataka, 2019). Additionally, four-week treatment with 800mg CBD reduced anxiety in people with a cannabis use disorder compared to placebo (Freeman et al, 2020). Therefore, repeated dosing of CBD may necessary to produce anxiolytic effects.…”
Section: Discussionmentioning
confidence: 99%